Responses of In vitro-Grown Plantlets (Vitis vinifera) to Grapevine leafroll-Associated Virus-3 and PEG-Induced Drought Stress - Cui, Zhen-Hua; Bi, Wen-Lu; Hao, Xin-Yi; Xu, Yan; Li, Peng-Min; Walker, M. Andrew; Wang, Qiao-Chun (Frontiers in Physiology, 2016)
Abstract Stresses caused by viral diseases and drought have long threatened sustainable production of grapevine. These two stresses frequently occur simultaneously in many of grapevine growing regions of the world. We studied responses of in vitro-grown plantlets (Vitis vinifera) to Grapevine leafroll associated virus-3 (GLRaV-3) and PEG-induced drought stress. Results showed that stress induced by either virus infection or drought had negative effects on vegetative growth, caused significant decreases and increases in total soluble protein and free proline, respectively, induced obvious cell membrane damage and cell death, and markedly increased accumulations of O2- and H2O2. Co-stress by virus and drought had much severer effects than single stress on the said parameters. Virus infection alone did not cause significant alternations in activities of POD, ROS and SOD, and contents of MDA, which, however, markedly increased in the plantlets when grown under single drought stress and co-stress by the virus and drought. Levels of ABA increased, while those of IAA decreased in the plantlets stressed by virus infection or drought. Simultaneous stresses by the virus and drought had co-effects on the levels of ABA and IAA. Up-regulation of expressions of ABA biosynthesis genes and down-regulation of expressions of IAA biosynthesis genes were responsible for the alternations of ABA and IAA levels induced by either the virus infection or drought stress and co-stress by them. Experimental strategies established in the present study using in vitro system facilitate investigations on ‘pure’ biotic and abiotic stress on plants. The results obtained here provide new insights into adverse effects of stress induced by virus and drought, in single and particularly their combination, on plants, and allow us to re-orientate agricultural managements towards sustainable development of the agriculture.